Exclusive breastfeeding during the 40-day rest period and at six months in Lebanon: a cross-sectional study - Rana F. Chehab; Lara Nasreddine; Racha Zgheib; Michele R. Forman (BMC, 2020)
Abstract Background Exclusive breastfeeding is recommended for the first 6 months of life with well-established benefits to the mother and child. The traditional practice of the 40-day rest period helps establish and maintain exclusive breastfeeding. This study aims to estimate the prevalence and examine the factors associated with exclusive breastfeeding at 40 days and at 6 months in Lebanon. Methods A cross-sectional survey was conducted in 2011-2012 as part of the "Early Life Nutrition and Health in Lebanon" study. A nationally representative sample of 1005 children aged five years or younger and their mothers was drawn from households using a stratified cluster sampling design. Trained nutritionists interviewed eligible mothers about sociodemographic characteristics of the household and maternal and child characteristics including infant feeding practices. Anthropometric measurements of the mother and child were collected. Multinomial logistic regression analysis was conducted to examine the characteristics associated with exclusive breastfeeding. Results The prevalence of exclusive breastfeeding was 41.5% at 40 days and 12.3% at 6 months. Children in families with three or more children had higher odds of exclusive breastfeeding for 40 days (Adjusted Odds Ratio [AOR] 1.76, 95% Confidence Interval [CI] 1.19, 2.60). Children in families owning two or more cars had lower odds of exclusive breastfeeding for 40 days (AOR 0.45, 95% CI 0.24, 0.83) and at 6 months (AOR 0.32, 95% CI 0.14, 0.77). Similarly, children delivered via Caesarian section had lower odds of exclusive breastfeeding for 40 days (AOR 0.49, 95% CI 0.34, 0.71) and at 6 months (AOR 0.39, 95% CI 0.24, 0.65). The odds of exclusive breastfeeding for 6 months were lower among children of overweight (AOR 0.50, 95% CI 0.26, 0.95) or obese (AOR 0.56, 95% CI 0.32, 0.98) mothers. Conclusions The association between higher socio-economic status, as reflected by car ownership, and C-section delivery with lower odds of exclusive breastfeeding persisted across the first 6 months in Lebanon. Future research should investigate the factors associated with exclusive breastfeeding in prospective cohort studies and help to better understand the cultural practice of the 40-day rest period in relation to breastfeeding.